Otolith Degeneration with Aging: Insights from Video Ocular Counter-Roll (vOCR) Assessment - Melissa Castillo-Bustamante; Jorge Madrigal; Elizabeth Andalón-Dueñas; Johanna Marcela Vanegas; Ireri Espinoza (Journal of Otology, 2025)
Background: Vestibular assessments, such as the video ocular counter roll (vOCR) test, offer valuable insights into the interactions between age, otolith function, and vestibular performance. Objective: To analyze the relation between age and vOCR gains as a potential marker of age-related otolith degeneration. Methods: A total of 107 participants underwent vOCR testing. Descriptive statistics and simple linear regression analyses were conducted to explore the association between age and vOCR gains. Results were presented using regression coefficients, 95% confidence intervals, p-values, and R-squared values. Results: In the overall sample, statistically significant associations were observed between age and vOCR gains in both ears. For the right ear, vOCR gains decreased with increasing age (coefficient: -0.03; 95% CI: -0.05 to -0.01; p <0.001; R² = 0.08), while the left ear showed a slightly stronger association (coefficient: -0.04; 95% CI: -0.07 to -0.02; p < 0.001; R² = 0.12). These findings indicate a moderate age-related decline in otolith-mediated vestibular responses. Conclusion: vOCR gains appear to decline with age, reflecting potential age-related otolith degeneration. These results support the clinical value of vOCR as a non-invasive method to assess vestibular function and its changes across the lifespan.